"I mark'd out a Semi-Circle for my Encampment" : l'empreinte de Robinson Crusoe sur l'île revisitée - Emmanuelle Peraldo (Caliban: French Journal of English Studies)
This article studies the interaction between Robinson Crusoe and the island to see how nature—the earth, trees and animals—responds to the more or less violent traces left by man in Daniel Defoe's novel (1719), from a footprint in the sand to stakes driven into the soil and trees cut for construction, and how Robinson (re-)writes the History of British imperialism and colonization through the way he occupies, transforms and reorients the environment and space of the island in order to maximize the exploitation of the resources of the island, as a mercantile capitalist at the beginning of the eighteenth century should do.